2018
DOI: 10.1051/0004-6361/201832911
|View full text |Cite
|
Sign up to set email alerts
|

Formation of S0 galaxies through mergers

Abstract: Context. Major mergers are popularly considered too destructive to produce the relaxed regular structures and the morphological inner components (ICs) usually observed in lenticular (S0) galaxies. Aims. We aim to test if major mergers can produce remnants with realistic S0 morphologies. Methods. We have selected a sample of relaxed discy remnants resulting from the dissipative merger simulations of the GalMer database and derived their properties mimicking the typical conditions of current observational data. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 271 publications
(213 reference statements)
4
67
0
Order By: Relevance
“…This paper was a proof of concept that major mergers can produce disc galaxies in the idealized scenario of two isolated galaxies, and allowed to study and follow in detail and in a controlled environment the formation of the disc. Similar work then followed, such as Tapia et al (2017), Eliche-Moral et al (2018) and Sauvaget et al (2018), who confirmed these results. However, such simulations are run in isolation, therefore they neglect the effect of the environment, and make assumptions on the parameters of the merger such as the orbit, or on the structures of the two merging galaxies.…”
Section: Introductionsupporting
confidence: 68%
“…This paper was a proof of concept that major mergers can produce disc galaxies in the idealized scenario of two isolated galaxies, and allowed to study and follow in detail and in a controlled environment the formation of the disc. Similar work then followed, such as Tapia et al (2017), Eliche-Moral et al (2018) and Sauvaget et al (2018), who confirmed these results. However, such simulations are run in isolation, therefore they neglect the effect of the environment, and make assumptions on the parameters of the merger such as the orbit, or on the structures of the two merging galaxies.…”
Section: Introductionsupporting
confidence: 68%
“…In addition, extensive irregular regions of dust extending about 6 kpc along the semimajor axis of the galaxy are observed. These structures, together with the presence of a disk of gas rotating in the opposite direction to the stellar component of the galaxy, provide evidence of a merger/interaction event in the recent past with an object of lower mass than NGC 4546 (Eliche-Moral et al 2018). In this context, the presence of the young NGC 4546-UCD1 with an age of ∼ 4 Gyr and with a rotation direction similar to the gas distribution, would be related to the aforementioned interaction event.…”
Section: Discussionmentioning
confidence: 80%
“…The current paradigm for galaxy formation, in particular of ETG, details the hierarchical assembly of massive galaxies via the merging of smaller systems, which result in expectedly pressure-supported systems due to the nature of the merging process (for instance, see Somerville & Davé 2015, and references therein for a general review). Merging during the lifetime of a galaxy is a key aspect, and often the focus, of many cosmological and/or hydrodynamical simulations (for example, see Bird et al 2013;Athanassoula et al 2016;Eliche-Moral et al 2018). Moreover, merging is often invoked to explain many phenomena seen in observational studies (for example, see Arnold et al 2011;Lidman et al 2013;Guérou et al 2016).…”
Section: Implications For the Formation History Of Ngc 3115mentioning
confidence: 99%